Environmental PM2.5 Exposure: An Ignored Factor Associated with Blood Cadmium Level in Hemodialysis Patients - Hsu CW; Chan MJ; Weng CH; Tsai TY; Yen TH; Huang WH (Therapeutics and Clinical Risk Management, 2025)
Ching-Wei Hsu,1,2 Ming-Jen Chan,1,2 Cheng-Hao Weng,1,2 Tsung-Yu Tsai,1,2 Tzung-Hai Yen,1,2 Wen-Hung Huang1,2 1Department of Nephrology and Clinical Poison Center, Chang Gung Memorial Hospital, Linkou Medical Center, Taoyuan, Taiwan, Republic of China; 2Chang Gung University, College of Medicine, Taoyuan, Taiwan, Republic of ChinaCorrespondence: Wen-Hung Huang, Department of Nephrology and Clinical Poison Center, Chang Gung Memorial Hospital, 199, Tung-Hwa North Road, Taipei, Taiwan, Republic of China, Tel +886-3-3281200-8181, Fax +886-3-3288662, Email williammedia@gmail.comBackground: The negative impacts of particulate matter with an aerodynamic diameter of 2.5 μm or less (PM2.5) are well known. Patients undergoing maintenance hemodialysis (HD) have significantly higher blood cadmium levels (BCLs) than healthy individuals. As elemental cadmium can be found in the PM2.5 particle fraction, we conducted this study to assess the effect of environmental PM2.5 exposure and other clinical variables on BCLs in maintenance HD patients.Patient and Methods:  This cross-sectional study included 754 hD patients who had previously participated in a BCL study. Demographic, hematological, biochemical and dialysis-related data were collected for analysis. For each patient, the mean PM2.5 concentrations in the living environment during the previous 12 and 24 months were recorded and analyzed.Results: Of all patients, the median BCL of was 0.36 μg/L (range: 0.21, 0.79 μg/L). The mean PM2.5 concentration was 28.45 ± 3.57 μg/m3 during the 12 months and 29.81 ± 3.47 μg/m3 during the 24 months, respectively. From a multivariate linear regression analysis, log BCL was positively associated with the mean PM2.5 concentration during the previous 12 and 24 months. In addition, log BCL was positively associated with the number of days with PM2.5 concentrations above the standard level during the previous 12 and 24 months. Moreover, according to the tertiles of days with a daily mean PM2.5 concentration above the normal limit in the previous 24 months, patients with the highest exposure days exhibited a significantly higher BCL than those in the other two patient groups.Conclusion: Chronic environmental exposure to PM2.5 is significantly associated with BCLs in maintenance HD patients, and exposure to PM2.5-bound cadmium may contribute to the harmful effects on health in this population. Further studies are needed to confirm these observations and to explore the underlying mechanisms.Keywords: air pollution, cadmium, hemodialysis, particulate matter, PM2.5